2021
DOI: 10.3389/fmolb.2021.743012
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Potential Autophagy-Related Biomarkers in Endometriosis by WGCNA

Abstract: Background: Endometriosis is a serious gynecological disorder characterized by debilitating pain, infertility and the establishment of innervated endometriosis lesions outside the uterus. Early detection and accurate diagnosis are pivotal in endometriosis. The work screened autophagy-related genes (ATGs) as potential biomarkers to reveal new molecular subgroups for the early diagnosis of endometriosis.Materials and Methods: The gene lists of ATGs from five databases were integrated. Then, weighted gene co-expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 46 publications
0
7
0
Order By: Relevance
“…However, the clinical significance and biological mechanism of lncRNA in the development of endometriosis remain largely unknown. There are reports in the scientific press suggesting a link between lncRNA expression and the development of endometriosis [ 5 , 6 , 7 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical significance and biological mechanism of lncRNA in the development of endometriosis remain largely unknown. There are reports in the scientific press suggesting a link between lncRNA expression and the development of endometriosis [ 5 , 6 , 7 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…In order to analyze the effect of different gene expression levels on patients with different subtypes of osteoporosis, the R package limma ( 22 ) was used to perform differential gene analysis between the two groups of patient samples in the integrated dataset. The significant differential genes (DEGs) were screened.…”
Section: Methodsmentioning
confidence: 99%
“…Nine recognized ubiquitination modes, based on connection sites, regulate the activation, localization, and interactions of various cellular proteins, influencing cell signaling, stress response, DNA repair, and implicated in various human diseases [ 24 ]. Recent research highlights the essential association between ubiquitination and endometriosis pathogenesis [ 25 ]. It was reported that ubiquitin was expressed in endometriotic cells and was associated with the survival of ectopic stromal cells in endometriosis [ 26 ].…”
Section: Introductionmentioning
confidence: 99%